Pengaruh Model Pembelajaran Project Based Learning Berbantuan Media Prezi terhadap Kemampuan Menulis Teks Prosedur pada Siswa Kelas VII SMP Negeri 29 Medan - Mutiara Salsabila Rangkuti; Muharrina Harahap (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Students experience difficulties in learning to write procedure texts. This is caused by students' interest in learning procedural text material which is still relatively low, students' lack of understanding in writing procedural texts, students are not enthusiastic about learning to write procedural texts. The aim of this research is to analyze (1) the ability to write procedural texts of class VII SMP students. Negeri 29 Medan before using the project based learning learning model assisted by Prezi media; (2) the ability to write procedural texts for class VII students at SMP Negeri 29 Medan after using the project based learning model assisted by Prezi media. (3) the influence of the project based learning model assisted by Prezi media on the ability to write procedural texts for class VII students at SMP Negeri 29 Medan. This research uses an experimental one group pre-test post-test design method. The results of the research show that 1) the ability to write procedural texts for class VII students at SMP Negeri 29 Medaln before implementing the project based learning learning model assisted by Prezi media was still classified as adequate in terms of category, with an average value of 60.16 while the majority of students had not yet reached the minimum completeness criteria. (KKM) which has already been determined by the school with a score of 76. 2) The ability to write procedural texts for class VII students at SMP Negeri 29 Medaln after implementing the Prezi media-assisted project based learning model is in the reverse category with a score of 84.35 based on the test t, with a significant level value of α = 0.05 and n = 31, the t-table value is 2.04. Therefore, it can be concluded that t-count > t-table, namely 7.15 > 2.04. This proves that there is a significant influence from the use of the project based learning model assisted by Prezi media on class VII students at SMP Negeri 29 Medan.